Increased plasma and salivary cortisol levels in patients with oral cancer and their association with clinical stage - Bernabé, Daniel Galera [UNESP]; Tamae, Adriano Caires [UNESP]; Miyahara, Glauco Issamu [UNESP]; Marcal Sundefeld, Maria Lucia [UNESP]; Oliveira, Sandra Penha [UNESP]; Biasoli, Eder Ricardo [UNESP] (B M J Publishing Group, 2012)
Objectives Dysregulation of the hypothalamus-pituitary-adrenal axis has been observed in patients with cancer. This cross-sectional study investigated whether patients with oral and oropharyngeal squamous cell carcinoma (SCC) show changes in cortisol levels in saliva and plasma compared with three control groups, and evaluated its correlation with clinicopathological data.Methods Salivary and plasma cortisol levels of 34 patients with oral SCC were compared with hormonal levels of 17 oropharyngeal SCC patients, 17 oral leukoplakia patients, 27 smokers and/or drinkers and 25 healthy volunteers. Multivariate analysis was used to evaluate the impact of clinical variables on the cortisol levels.Results The plasma (p<0.05) and salivary (p<0.01) cortisol levels were significantly higher in patients with oral SCC compared with all groups. Patients with oropharyngeal SCC had higher levels of salivary cortisol compared with smokers and/or drinkers (p<0.05) and patients with leukoplakia (p<0.01). Patients with advanced-stage oral SCC showed significantly higher levels of cortisol than those in an initial clinical stage. Men with oral SCC had higher salivary cortisol levels than women (p<0.05). Age, smoking, alcohol consumption, presence of teeth and awareness of cancer diagnosis had no significant effect on cortisol levels.Conclusions These results indicate a dysregulation of cortisol secretion in patients with oral cancer and suggest that this hormone can be a biomarker associated with the disease's clinical status.